The Effect of Concentration of Beeswax Emulsion on Shelf Life and Quality of Beetroot (Beta vulgaris L.) during Room Temperature Storage - Pratiwi, Vera Handi; Handoko, Yoga Aji (Jurnal Sains dan Teknologi Pangan, 2021)
Beetroot (Beta vulgaris L.) is one of the horticultural products that have the potential for development in Indonesia. beetroot contains a high level of betalain and vitamin C, so it can be an antioxidant for cancer. But nowadays, post-harvest handling is not specially noticed by people yet. The aims of this research were to determine the effect of beeswax coating on shelf life and quality of the beetroot and determine the best wax emulsion concentration as beetroot coating. This research was conducted at the Posharvesting Handling Laboratory of the Faculty of Agriculture and Business, Satya Wacana Christian University, Salatiga. The method used Randomized Block Design with 4 treatments and 6 replications. The concentration of beeswax emulsions used in this research is about 4%, 8%, and 12%. The observed parameter was weight loss, respiration, total dissolved solids, water content, and vitamin C. The results show that the treatment with a concentration of 12% of beeswax emulsion is the best result when compared with other treatments. The result also shows the concentration of 12% beeswax emulsion can maintain the storage time and quality of the beetroot.